2022
DOI: 10.2147/dddt.s350913
|View full text |Cite
|
Sign up to set email alerts
|

A Potent EGFR Inhibitor, N-Phenyl Pyrazoline Derivative Suppresses Aggressiveness and Cancer Stem Cell-Like Phenotype of Cervical Cancer Cells

Abstract: Objective Metastasis causes approximately 90% of cancer-related deaths, including in cervical cancer patients. Uncontrolled cell proliferation, migration, and cancer stemness act as critical events in primary tumor growth and cancer metastasis progression in cervical cancer. Here, we investigated the anti-proliferative, anti-migration, and cancer stemness inhibition activity of N-phenyl pyrazoline derivatives against cervical cancer cells. Methods The chalcone and pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…On the other hand, compound 55 b suppressed the EGFR expression level but not the total ERK1/2. The docking analysis revealed that compound 55 b displays a improved binding affinity to the EGFR than the EGFR inhibitor (erlotinib) [127] …”
Section: Recent Development Of Different Nitrogen Containing Derivati...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, compound 55 b suppressed the EGFR expression level but not the total ERK1/2. The docking analysis revealed that compound 55 b displays a improved binding affinity to the EGFR than the EGFR inhibitor (erlotinib) [127] …”
Section: Recent Development Of Different Nitrogen Containing Derivati...mentioning
confidence: 99%
“…The docking analysis revealed that compound 55 b displays a improved binding affinity to the EGFR than the EGFR inhibitor (erlotinib). [127] [128] In 2019, George and group reported the pyrazoline clubbed quinoline hybrid and appraised against anti-tumor potential. The in vitro assessment of SRB assay against MCF-7), HeLa and DLDI specified that nearly all the candidate showed noticeable inhibitory effect with IC 50 ranging from 0.064-4.94, 0.12-6.273 and 0.038-3.155 μM respectively.…”
Section: Pyrazolinementioning
confidence: 99%
“…In the previous study, we found a small compound, N -phenyl pyrazoline inhibits one of the protein kinases, EGFR leads to cervical cancer aggressiveness attenuation 6 . N -phenyl pyrazoline also inhibits the cell viability of human breast cancer cells and colorectal cancer cells 7 .…”
Section: Introductionmentioning
confidence: 98%
“…[13][14][15] This compound also induces poor survival, reduces tumor sphere size, inhibits cell growth, and reduces CD133 levels in HeLa cervical cancer cell lines. 14,16 We successfully showed a decrease in EGFR (Epidermal Growth Factor Receptor) levels in HeLa cells induced by an N-phenyl pyrazoline derivate. 13,16,17 Therefore, the N-phenyl pyrazoline derivative is a promising anticancer drug and potential to be combined with other anticancer drugs to increase their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…14,16 We successfully showed a decrease in EGFR (Epidermal Growth Factor Receptor) levels in HeLa cells induced by an N-phenyl pyrazoline derivate. 13,16,17 Therefore, the N-phenyl pyrazoline derivative is a promising anticancer drug and potential to be combined with other anticancer drugs to increase their effectiveness. We previously reported that a compound belonging of N-phenyl pyrazoline derivates, Pyrazoline B (methoxyphenyl)-1-phenyl-3-(thiophen-2-yl) −4,5-dihydro-1H-pyrazole), exerts promising anticancer activity based on in silico 18 and in vitro 19 studies.…”
Section: Introductionmentioning
confidence: 99%